Chinese Aid to Latin America and the Caribbean: Evolution and Prospects - Lorenzo Maggiorelli (Revista Internacional de Cooperación y Desarrollo)
In the last decade, China has risen as a very visible player in Latin America and the Caribbean (LAC), through its foreign aid, its investments and its bilateral trade. While extensive research has been conducted on Chinese aid to Africa, this paper will focus instead on the Chinese aid to LAC. After an overview of the historical evolution of Chinese aid to the region, and an attempt to quantify the amount of Chinese aid received by LAC as compared to other developing regions, this paper considers the three main motives which may drive China to provide aid, such as the needs of the recipient, the institutional characteristics of the beneficiary, and the political and economic interests of the donor country. The article concludes with an appraisal of the potential benefits and negative impacts of the Sino-LAC relationship, finding among potential concerns the unconditionality of Chinese foreign aid and its unbalanced trade relationship with the region.